2012
DOI: 10.3892/ol.2012.1096
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ERCC1 expression levels on the chemosensitivity of gastric cancer cells to platinum agents and survival in gastric cancer patients treated with oxaliplatin-based adjuvant chemotherapy

Abstract: Excision repair cross-complementing 1 (ERCC1) is reported to be involved in the sensitivity of cancer cells to platinum-based chemotherapy. The present study was designed to evaluate the effects of ERCC1 expression on the chemosensitivity of platinum agents in gastric cancer cell lines, and on survival in gastric cancer patients treated with surgery followed by oxaliplatin-based adjuvant chemotherapy. ERCC1 expression levels were measured by quantitative reverse transcription-polymerase chain reaction (qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…Univariate analyses revealed that patients with low ERCC1 levels had longer relapse-free survival (RFS) and OS than those with high ERCC1 levels (median RFS, 18 vs 7 months, P = 0.001; median OS, 27 vs 11months, P = 0.001). It was concluded that gastric cancer patients with low levels of ERCC1 expression demonstrated a benefit from oxaliplatin-based adjuvant chemotherapy (Liu et al, 2013). In our study, the association between ERCC1 expression in tumor tissues and outcome in resected patients treated with oxaliplatin-based regimens confirms what has been described by other authors.…”
Section: Discussionsupporting
confidence: 81%
“…Univariate analyses revealed that patients with low ERCC1 levels had longer relapse-free survival (RFS) and OS than those with high ERCC1 levels (median RFS, 18 vs 7 months, P = 0.001; median OS, 27 vs 11months, P = 0.001). It was concluded that gastric cancer patients with low levels of ERCC1 expression demonstrated a benefit from oxaliplatin-based adjuvant chemotherapy (Liu et al, 2013). In our study, the association between ERCC1 expression in tumor tissues and outcome in resected patients treated with oxaliplatin-based regimens confirms what has been described by other authors.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to in NSCLC, ERCC1 has been found to be a negative predictive factor in a European population receiving adjuvant cisplatin-based chemotherapy after gastrectomy because ERCC1 negativity was associated with longer OS [134]. Similar results were seen in an Asian population that received adjuvant oxaliplatinbased chemotherapy [135]. Again, similar to the data seen in NSCLC, elevated ERCC1 was a positive prognostic biomarker in patients who did not receive adjuvant chemotherapy after resection and a negative predictive marker in patients who received chemotherapy after gastrectomy [136].…”
Section: Potential New Targetssupporting
confidence: 71%
“…High ERCC1 expression has been demonstrated to be associated with resistance to platinum-based chemotherapy and worse prognosis in cancer patients [20,37,38]. To this aim, we here assessed that the ERCC1 gene polymorphisms may play an analogous clinical role as predictive and prognostic factor among patients with T4 breast cancer receiving platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%